Erythema Multiforme Major Caused by Amoxicillin and Ceftriaxone in Patient Suffering from Respiratory Infection: A Case Report - Amir, Mohammad; Vohra, Manisha; Sharma, Amit; Osoro, Ian (Indian Journal of Pharmacy Practice)
Erythema Multiforme (EM) is an acute, self-limited, and occasionally recurrent skin disorder that is caused by a variety of infections, drugs, and other stimuli. Infections account for 90% of cases of erythema multiforme, which is brought on by a cell-mediated immune response. The adverse drug reaction reported is rare and is caused by amoxicillin and ceftriaxone. A 49-year old male patient visited the outpatient department with a chief complaint of breathlessness, cough, dyspnea, fever, itching, redness, and skin allergic reaction on the stomach, hands, and legs. He has had a history of type 2 Diabetes Mellitus (DM) from the past eight years. He had been prescribed oral amoxicillin 875 mg twice a day, ceftriaxone 2g/daily, paracetamol 625mg (SOS), pantoprazole 40mg/daily, and multivitamin once a day for a chest infection, and metformin 500mg + glimepiride 2mg in morning and insulin glargine 10 IU (SOS) for type-II diabetes. On the assessment of causality this Adverse Drug Reaction (ADR) was found probable by both the WHO-UMC scale and Naranjo scale. It was observed that ADRs like blisters following erythema multiforme major can be lethal and can cause anxiety and stress to the patients and also their quality of life is reduced. This present case report will help the physicians, clinicians and other healthcare professionals to get aware and vigilant about the adverse drug reaction caused by amoxicillin and ceftriaxone and also helps them in the early detection and management of ADR.
Keywords: Erythema multiforme major; Adverse drug reaction; Amoxicillin; Ceftriaxone; Case report